2014
DOI: 10.1007/s13197-014-1390-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aqueous extracts of Mentha arvensis (mint) and Piper betle (betel) on growth and citrinin production from toxigenic Penicillium citrinum

Abstract: Due to growing concern of consumers about chemical residues in food products, the demand for safe and natural food is increasing greatly. The use of natural additives such as spices and herbal oil as seasoning agents for their antimicrobial activity has been extensively investigated. This paper discusses the efficacy of the aqueous extract of mint (Mentha arvensis) and betel (Piper betle) on the mycelial growth and citrinin production of Penicillium citrinum. The present investigation revealed that mint extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…It reduced OTA production by up to 70% without affecting the fungal dry weight. These results are similar to those obtained by Panda et al [ 20 ] who found that the phenolic extracts from Mentha arvensis , commonly known as mint leaves, highly reduced the citrinin production by P. citrinum without truly affecting its growth. The use of the mint EO at 0.5 µL mL −1 allowed the growth of A. ochraceus with no detectable OTA in the culture medium [ 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…It reduced OTA production by up to 70% without affecting the fungal dry weight. These results are similar to those obtained by Panda et al [ 20 ] who found that the phenolic extracts from Mentha arvensis , commonly known as mint leaves, highly reduced the citrinin production by P. citrinum without truly affecting its growth. The use of the mint EO at 0.5 µL mL −1 allowed the growth of A. ochraceus with no detectable OTA in the culture medium [ 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…2. This was consistent with the findings of Panda et al (2015), who investigated the production of citrinin by Penicillium citrinum, extracted from peppermint leaves. All concentration levels of extracts from peppermint leaves (0.21 µg/mL, 0.42 µg/mL, 0.63 µg/mL, 0.84 µg/mL) reduced the production of citrinin.…”
Section: Types Of Phenolic Compounds In Inhibition Of Fungal Growthsupporting
confidence: 92%
“…The final concentration of the extracts in the wells was 1 mg/mL, while ciprofloxacin at a concentration of 2,5 μg/mL and amphotericin B at 5 μg/mL were used as the positive controls for P. aeruginosa and C. albicans , respectively [ 160 ]; for the other microorganisms, the control samples were the same culture media but without M. × piperita [ 161 ]. Panda et al [ 162 ] showed that M. arvensis aqueous extract at 0.8 mg/mL inhibited citrinin production by P. citrinum up to 73% (positive control: none).…”
Section: Food Preservative Applications Of Genus Mentha mentioning
confidence: 99%